2014
DOI: 10.1016/j.chemosphere.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of manganese metallodrugs toward Danio rerio

Abstract: Manganese is an essential metal which can be neurotoxic in some instances. As Mn-based metallodrugs are ever more prevalent in clinical practice, concern regarding the toxic effects of Mn discharges to water bodies on the biota prompted us to study the physicochemical parameters of these complexes and to assess their acute toxicity toward adult Danio rerio individuals, particularly in terms of brain tissue damage. Our results show that the Mn(III)-salen acetate complex EUK108 is toxic, which can be rationalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In this case, the antioxidant catalyst showed a positive effect on sarcoplasmic reticulum Ca 2+ release in Wistar rats but a negative effect on myofibrillar Ca 2+ sensitivity. On the other hand, Espósito et al [ 162 ] reported the toxicity of EUK-108 (20–100 µM dose) toward Danio rerio individuals (zebrafish), particularly in terms of brain damage. Finally, Vanfleteren et al [ 11 ] found that administration of EUK-8 to starving Escherichia coli cells surprisingly enhanced the production of ROS, resulting in a massive increase of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the antioxidant catalyst showed a positive effect on sarcoplasmic reticulum Ca 2+ release in Wistar rats but a negative effect on myofibrillar Ca 2+ sensitivity. On the other hand, Espósito et al [ 162 ] reported the toxicity of EUK-108 (20–100 µM dose) toward Danio rerio individuals (zebrafish), particularly in terms of brain damage. Finally, Vanfleteren et al [ 11 ] found that administration of EUK-8 to starving Escherichia coli cells surprisingly enhanced the production of ROS, resulting in a massive increase of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…P2 also presented high levels of manganese. The toxicity of manganese in fish depends on species and, within a species, depends on the tissue, and this metal decreased the activity of CAT and SOD in the brain of some species of fish (Vieira et al, 2012;Arndt et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the antioxidant catalyst showed a positive effect on sarcoplasmic reticulum Ca 2+ release in Wistar rats but a negative effect on myofibrillar Ca 2+ sensitivity. On the other hand, Espósito et al [166] reported the toxicity of EUK-108 (20-100 M dose) toward Danio rerio individuals (zebrafish), particularly in terms of brain damage. Finally, Vanfleteren et al [11] found that administration of EUK-8 to starving Escherichia coli cells surprisingly enhanced the production of ROS, resulting in a massive increase of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%